Analisis Fundamental Makro, Struktur Modal Terhadap Nilai Perusahaan Dengan Struktur Kepemilikan, Kinerja Keuangan, Karakteristik Perusahaan Sebagai Variabel Intervening Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Salma Dewi Ambarsari; Hwihanus Hwihanus (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
By considering the role of intervening variables, such as ownership structure, financial performance, and company characteristics, this study aims to analyze the impact of macro fundamentals, capital structure, and on firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The analytical tool used is Smart-PLS and descriptive quantitative methodology. This study states that ownership structure, macro fundamentals, and capital structure insignificantly affect firm value. In addition, an examination of intervening variables reveals that, in contrast to business characteristics, ownership structure and financial performance moderate the relationship between macro fundamentals, capital structure, and firm value. These results imply that macro fundamentals, capital structure, ownership structure, and financial performance should be considered in evaluating firm value. These results highlight the importance of maintaining an ideal capital structure and improving financial performance for firms to increase firm value.